MODEL POINT OF BALANCE IN DECISION -MAKING - Santos Jiménez, Néstor (1999)
Every company develops between two markets : suppliers and consumers; is responsible for transforming inputs into outputs , generating added value to justify the investment. The cost structure and expenses during the operation of the company allows to view, in a defined market, minimal effort is needed to develop to cover this effort , so that any additional production will be a monetary gain. This minimum level is the equilibrium point, which depends on the cost of inputs and the sale price of the products.The effect of variation of the factors that determine the equilibrium point is not uniform, depends on the structure of costs and expenses and variable contribution margin per unit , the sensitivity of the equilibrium volume facilitates prioritization decisions that the company must take into appropriate and timely manner.